2016
DOI: 10.1016/j.jsxm.2016.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Female Partners of Men with Peyronie's Disease Have Impaired Sexual Function, Satisfaction, and Mood, While Degree of Sexual Interference Is Associated with Worse Outcomes

Abstract: Introduction Peyronie's disease (PD) causes penile deformity and can result in sexual dysfunction and psychological distress. Currently, nothing is known about the psychosexual impact on the partners of men with PD. Research carried out on the partners of men with other chronic illnesses suggests that the partners of men with PD might have increased rates of sexual dysfunction and decreased sexual satisfaction. Aims To examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Penile curvature and pain during erection present a significant bothersome issue for both men with PD and their partner [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Penile curvature and pain during erection present a significant bothersome issue for both men with PD and their partner [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports have suggested that up to 54% of men with PD have relationship problems, with risk factors being loss of penile length, low libido and penile pain ( 5 ). Female partners of men with PD have also been found to have decreased sexual function, sexual satisfaction and mood compared with population-based norms ( 10 ). Partners may also directly impact the patients’ decisions to correct their deformities, which is supported by our finding that those experiencing partner pain were more likely to consider surgical intervention or other invasive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…11 Numerous studies have now demonstrated significant distress in patients suffering with PD as well as their partners (both heterosexual and same sex partnerships). [12][13][14] Other studies have demonstrated significant findings on depression scales, with Nelson et al reporting that 47% of men with PD reported clinically meaningful depression. [15][16] Men with PD report embarrassment and shame, and may avoid sexual relationships; this may take a tremendous toll on their quality of life.…”
Section: Peyronie's Disease and Qol Impactmentioning
confidence: 99%